VD_FINDINFO HC / 2014 / 331 vom 6. Mai 2014 - VD Tribunal cantonal (2014)
BAIL À LOYER, VALEUR LITIGIEUSE, COMPÉTENCE RATIONE MATERIAE | 107 al. 2 CPC (CH), 209 CPC (CH), 212 CPC (CH), 308 al. 2 CPC (CH), 310 CPC (CH), 92 al. 1 CPC (CH)